Effect of therapeutic plasma exchange on immunoglobulins in myasthenia gravis. (2nd October 2016) - Guptill, Jeffrey T.; Juel, Vern C.; Massey, Janice M.; Anderson, Amanda C.; Chopra, Manisha; Yi, John S.; Esfandiari, Ehsanollah; Buchanan, Tim; Smith, Bryan; Atherfold, Paul; Jones, Emma; Howard, James F.
Abstract: An integrated understanding of therapeutic plasma exchange (TPE) effects on immunoglobulins, autoantibodies, and natural or acquired (vaccine) protective antibodies in patients with autoimmune myasthenia gravis (MG) is lacking. Prior studies measured TPE effects in healthy volunteers or heterogeneous autoimmune disease populations. We prospectively profiled plasma IgA, IgM, IgG, IgG subclasses (IgG1–4), acetylcholine receptor autoantibodies (AChR+), and protective antibodies in patients with AChR + MG receiving TPE for an exacerbation. TPE was performed according to institutional practice and patients were profiled for up to 12 weeks. Ten patients were enrolled (median age = 72.9 years; baseline MG-Composite = 21; median TPE treatments = 6 during their first course) and all improved. The maximum decrease in all immunoglobulins, including AChR autoantibodies, was achieved on the final day of the first TPE course (∼60–70% reduction). Three weeks post-TPE, mean AChR autoantibody, total IgG, IgG1, and IgG2 titers were below the reference range and had not recovered within 20% of baseline, whereas other measured immunoglobulins approached baseline values. We did not generally observe an "overshoot" of immunoglobulins above pre-TPE levels or accelerated recovery of pathologic AChR autoantibodies. Protective antibody profiles showed similar patterns as other IgGs and were detectable at levels associated with protection from infection. A slow return to baseline for IgGs (except IgG3) was observed, and we did not observe any obvious effect of concomitant medications on this recovery. Collectively, these findings enhance our understanding of the immunological effects of TPE and further support the concept of rapid immunoglobulin depletion for the treatment of patients with MG.